A comparative study of the educational competency level (planning, evaluation) among teachers of physical education and sports in the secondary stage, depending on the experience‘ variable - Cherifi , Walid; Bouarouri , djaafar (sports creativity, 2025)
This study has aimed to identify the difference in the level of educational competency (planning and evaluation) between teachers of physical education and sports at the secondary level, according to the variable of experience, we have choosen a stratified random sample of 36 teachers, from a total of 124 teachers in some secondary schools in Biskra. We have used the comparative descriptive approach and educational competency scale. For the purpose of interpretation and analysis, we have used the T test. The researchers concluded that there is a difference in the level of educational competency (planning and evaluation) between physical education and sports teachers at the secondary stage, depending on the experience variable